2005
DOI: 10.1634/stemcells.2004-0125
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Neurogenic Mesenchymal Stem Cells in Human Scalp Tissue

Abstract: Recent studies have shown that adult tissues contain stem/ progenitor cells capable of not only generating mature cells of their tissue of origin but also transdifferentiating themselves into other tissue cells. Murine skin-derived precursor cells, for example, have been described as unique, nonmesenchymal-like stem cells capable of mesodermal and ectodermal neurogenic differentiation. Human-derived skin precursors are less well characterized.In this study, the isolation and characterization of adherent, mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(145 citation statements)
references
References 36 publications
2
135
0
7
Order By: Relevance
“…Several laboratories have now reported the existence of a multipotent dermal precursor cell population, the skin-derived precursor (SKP) cells (reviewed by Miller and coworkers [20,41]). Initially derived from rodents, now several groups reported isolation of SKPs from human scalp, foreskin, arm, beard and chin, in subjects ranging from fetal to old age [22,23,30,31,34,[36][37][38][39]. Transplantation of SKPs to animal models of disease has raised expectations for their potential use in human cell therapy [23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several laboratories have now reported the existence of a multipotent dermal precursor cell population, the skin-derived precursor (SKP) cells (reviewed by Miller and coworkers [20,41]). Initially derived from rodents, now several groups reported isolation of SKPs from human scalp, foreskin, arm, beard and chin, in subjects ranging from fetal to old age [22,23,30,31,34,[36][37][38][39]. Transplantation of SKPs to animal models of disease has raised expectations for their potential use in human cell therapy [23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Human SKPs have been previously derived from scalp [22,34,37,38], foreskin [30,36], arm [39], and the facial area [22]. However, there has been little or no phenotypic characterization of the SKPs isolated from these areas.…”
Section: Derivation and Phenotypic Characterization Of Human Skps Fromentioning
confidence: 99%
“…The authors claimed that these cells proliferated and differentiated in culture to produce both neural and mesodermal cell types, including neurones, glia, smooth muscle and adipocytes. Although MSCs can also be isolated from skin (Shih et al, 2005), the authors suggested that, being nestin-positive, skin-derived precursors (SKPs) are a different type of stem cell (Toma et al, 2001). The majority of neural cells generated by SKPs are similar to peripheral neurones and Schwann cells.…”
Section: Skin-derived Precursor (Skp) Stem Cellsmentioning
confidence: 99%
“…These neural crest related ASC can also be isolated from skin of the abdomen [30], breast [30], arm [31], face [32], and scalp [33] mostly upon aesthetic interventions. These cells have a high self-renewal and high multipotent differentiation capacity.…”
Section: Introductionmentioning
confidence: 99%